Hiring of Flexible and Fixed-term Workers in Five Norwegian and Swedish Industries - Svalund, Jørgen; Peixoto, Anna; Dølvik, Jon Erik; Jesnes, Kristin (Nordic Journal of Working Life Studies, 2018)
Analyzing how and why employers use fixed-term contracts or alternative forms of flexible, shortterm labor in five labor-intensive industries in Norway and Sweden, the main research question in this article is how employer hiring of temporary labor is affected by differences in national employment regulations and industries. Regarding employer motives, we find strong and similar inter-industry differences across the two countries, while the share of fixed-term employees is generally higher in Sweden than in Norway where regulations are stricter. Further, employers’ hiring of fixed-term labor is contingent on their access to alternative sources of flexible labor when faced with shifting demand, need for substitutes, or complex shift plans. The mix of fixed-term labor, agency workers, and use of extra part-time work also varies across industries, depending on the pattern of production, work organization, and workforce gender profile.